Efficacy and tolerability of triple drug therapy with albendazole, pyrantel pamoate, and oxantel pamoate compared with albendazole plus oxantel pamoate, pyrantel pamoate plus oxantel pamoate, and mebendazole plus pyrantel pamoate and oxantel pamoate against hookworm infections in school-aged children in Laos: a randomised, single-blind trial. Issue 7 (July 2018) - Moser, Wendelin; Sayasone, Somphou; Xayavong, Syda; Bounheuang, Bangon; Puchkov, Maxim; Huwyler, Jörg; Hattendorf, Jan; Keiser, Jennifer
Summary: Background: Albendazole and mebendazole are commonly used to control hookworm, but have shortcomings in their efficacy profiles. We assessed whether triple drug therapy (TDT) with albendazole, pyrantel pamoate, and oxantel pamoate was more effective than the co-administration of two drugs for the treatment of hookworm infections. Methods: A randomised, single-blind trial was done from Sept 27 until Nov 17, 2017, in Laos. Children (6–15 years) from six schools were invited to participate. Hookworm-positive children were randomly assigned (2:2:1:1) by a computer stratified list (block sizes of six and 12) to TDT with albendazole (400 mg), pyrantel pamoate (20 mg/kg), and oxantel pamoate (20 mg/kg); albendazole plus oxantel pamoate; pyrantel pamoate plus oxantel pamoate; or mebendazole (500 mg) combined with both pyrantel pamoate and oxantel pamoate (used as proof of concept to compare the two TDTs). Two stool samples were collected at baseline and follow-up (17–30 days after treatment) and analysed with the Kato-Katz method. The primary outcome was the proportion of hookworm egg-negative children at follow-up in all Kato-Katz slides (cure rate [CR]) in the TDT with albendazole, pyrantel pamoate, and oxantel pamoate group compared with the albendazole plus oxantel pamoate and pyrantel pamoate plus oxantel pamoate groups. Secondary outcomes were tolerability 3 h and 24 h after treatment, egg reduction rates (ERRs) against hookworm, and efficacy against concomitant soil-transmitted helminth infections. Participating children and field and laboratory technicians were masked to treatment allocation. All children with follow-up data were included in the primary analysis. This trial is registered withClinicalTrials.gov, numberNCT03278431 . Findings: 1529 children were assessed for eligibility, of whom 533 provided complete baseline data and 414 provided complete outcome data. The CR was higher for the TDT albendazole, pyrantel pamoate, and oxantel pamoate (116 [84%] of 138) than with albendazole plus oxantel pamoate (73 [53%] of 138; odds ratio 4·7, 95% CI 2·7–8·3; p<0·0001) and pyrantel pamoate plus oxantel pamoate (36 [52%] of 69; 4·8, 2·5–9·3; p<0·0001). The geometric ERR of the TDT albendazole, pyrantel pamoate, and oxantel pamoate (99·9%) was higher than that for albendazole plus oxantel pamoate (99·0%; difference in ERR 0·9 percentage points, 95% CI 0·5–1·4), and pyrantel pamoate plus oxantel pamoate (99·2%; 0·7 percentage points, 0·3–1·3). Adverse events were reported by six (1%) children 3 h and none 24 h after treatment, without any difference across treatment groups. Interpretation: TDT with albendazole, pyrantel pamoate, and oxantel pamoate could make a difference, in particular in the context of soil-transmitted helminth elimination. Pyrantel pamoate might be a useful alternative to prevent benzimidazole resistance; however, larger trials are needed to confirm this finding. Funding: Swiss National Science Foundation.